PEMANFAATAN TEPUNG AMPAS KELAPA (Cocos Nucifera Lin) DALAM PEMBUATAN COOKIES SAGU (Metroxylon Sagus Rottb) TERHADAP UJI ORGANOLEPTIK DAN DAYA TERIMA PADA ANAK USIA SEKOLAH - Hayatun Nufus, (Journal of Innovation Research and Knowledge, 2025)
Malnutrition among school-age children remains a challenge in Indonesia, including Riau Province. One strategy is providing supplementary foods from nutrient-rich local ingredients. Coconut pulp often treated as waste, still contains carbohydrates, protein, fat, fiber, and iron. Sago is an abundant local carbohydrate source, cookies were selected as the fortification medium because they are popular among children and. To evaluate the effect of coconut pulp flour addition on the organoleptic properties and acceptability of sago cookies. This experimental study applied a Completely Randomized Design (CRD) with four formulations of sago flour:coconut pulp flour, namely P0 (100:0), P1 (80:20), P2 (60:40), and P3 (50:50). Organoleptic tests (aroma, color, taste, texture) involved 56 semi-trained panelists, while acceptability testing was carried out with 29 children aged 10–12 years. Nutrient content was analyzed by proximate methods, and iron was measured using Atomic Absorption Spectrophotometry (AAS). Data were analyzed using the Kruskal–wallis and Post-hoc tests at a 5% significance level. Coconut pulp flour significantly affected taste and texture (p<0.05), but not aroma or color (p>0.05). The best formulation was P1 (80:20), with an average organoleptic score of 4.01. Nutrient composition of P1 included: carbohydrates 44,4%, protein 5.22%, fat 26.69%, iron 29.03 mg, dietary fiber 18.72%, moisture 5.91%, ash 1.62%, and crude fiber 4,16%. Acceptability testing indicated most children rated P1 as “good.” Formulation P1 yielded cookies that were organoleptically well-accepted, with high levels of iron and dietary fiber, and demonstrated potential as a functional snack derived from local food sources. Subsequent studies are recommended to focus on stabilizing moisture content in accordance with SNI standards, as well as conducting interventions among malnourished children and adolescent girls at risk of anemia, in order to investigate the potential of these cookies in supporting the fulfillment of iron requirements